Accelerated shelf life testing of bottled shrimp condiment - Ong, Daphne Barcelona
The study aimed to establish the shelf life of bottled shrimp condiment using accelerated shelf life testing. Microbiological tests conducted before incubation deemed the product stable. Physico-chemical and sensory evaluation tests were conducted every ten days until the products were considered spoiled. Microbiological tests were also done to confirm the physico-chemical and sensory evaluation tests results. The samples stored at 40°C and 55°C were established as unstable after forty and thirty days of storage, respectively. Using the shelf life plot and Arrhenius equation, the shelf life of bottled shrimp condiment at room temperature was estimated to be 50 to 52 days.